Effects of Modification behavior in New Normal of Life Program from the Situation of the Corona Virus 2019 of Employees of the Private Company in Ratchaburi Province - Ketphan, Ornpicha; Vipakul , Supatsara; Hangnaren, Bunyapuk; Samsalee, Benjawan (Journal of The Royal Thai Army Nurses, 2023)
The purpose of this research was a quasi-experimental design, a one-group study, 2 times. The objective was to compare the results before and after using the new normal life behavior change program from the Coronavirus Disease 2019. The sample group were 184 employees of private companies in Ratchaburi province. The sample size was calculated by the formula G*Power. easy Apply the concepts of learning theory and perception theory. which in the behavior change program, new way of life, there are activities as follows: 1) Creating awareness and exchanging situations 2) Educating on dangers, impacts and prevention guidelines. 3) Data access 4) Promote self-management 5) Exchange knowledge on self-management 6) Promote communication skills The tools used consisted of 4 parts: knowledge about the disease, attitude, perception and behavior. The validity of the content was examined by 3 experts, the accuracy was 0.86, 0.84 and 0.80. The statistics used to analyze the data were frequency, percentage, mean, standard deviation and Paired t-test. The research results showed that self-protection knowledge from disease, attitude, perception, and disease prevention and control behavior. Before and after using the program are different, with statistical significance at the .05 level which can be used as a way to prevent the spread of infection Raise the quality of preventive measures for company employees. And can expand the results and promote disease prevention activities. To help reduce the spread of the corona virus 2019.